Effect of Urethane Foam Cushioning on Structure-Borne Sound Transfer by a Slab with Panel Flooring - MU, RuiLin; TOYODA, Masahiro; TAKAHASHI, Daiji (Archives of Acoustics, 2016)
Urethane foam mattresses are commonly used as cushioning when placing panel flooring on the floor slab of a building. Urethane foam consists of elastic fibrefibres with pores. Both elements can affect the performance of the insulation against impact sounds. However, these effects have not yet been detailed, and they may change if the material properties or constitution of the fibres and pores in the cushioning change. In this paper, we propose an analytical model for use in evaluating the performance of insulation against floor impact sound. This model was used to examine the contribution of the pores versus the elastic fibres to wave transmissions from the flooring surface to the slab. The results reveal that the constitution of the foam (either open or closed cells of pores) and the thickness and hardness of the cushion layer strongly affect the sound insulation performance of the floor.